Morphological and morphometric identification of snapper (Family Lutjanidae) that landed in the Pulau Balai Fishing Port, Aceh Singkil - Erima, Derila; Bahri, Samsul; Rizal, Muhammad (Arwana: Jurnal Ilmiah Program Studi Perairan, 2024)
Pulak Banyak are one of the areas in Indonesia that have potential fishery resources. Accurate range determination and species identification are essential parts of fisheries resource management and must be done. This study aims to obtain information on the various types of snapper landed through morphological and morphometric approaches. The research was conducted in Fishing Port, Pulau Balai village, Pulau Banyak sub-district from September to October 2023. The method used in this research is descriptive analysis to describe fish morphology and measure several morphometric characteristics of fish. There were 12 characters measured using a ruler. The results of the study found ten species of 2 genera part of the family Lutjanidae with 36 individuals landed at the study site, namely Lutjanus synergies, Pristipomoides typus, Lutjanus vitta, Lutjanus madras, Lutjanus argentimaculatus, Lutjanus decussatus, Lutjanus erythropterus, Lutjanus gibbus, Lutjanus malabaricus, and Lutjanus papuensis. All fish species encountered have different morphological and morphometric characteristics, and the bambangan fish (Lutjanus erythropterus) is the fish with the largest morphometric size in the study site.